Geotechnical Investigation and Microanalysis of Black Cotton Soil Amended with Guar Gum and Polyethylene Terephlate Fibre - S. Sathyapriya; M. S. Abdul Fasith; P. Senthil Kumar; V. Karthik (International Journal of Chemical Engineering)
Polymer-based soil stabilization has fascinated substantial interest in the field of research intending to gain a better knowledge of the anticipated soil characteristics after polymer treatment. Intricate research on the engineering performance of expansive soil which is highly challenging due to its swell and shrink nature based on variations in water regime, treated with guar gum, a biopolymer made from gum along with polyethylene terephthalate fibre, one of the most generated plastics, resulting in massive waste, is accomplished through this entire experimental investigation. Comprehensive geotechnical tests and microstructural examinations have been performed to optimize the guar gum for enhancement of soil properties and to comprehend the interactive mechanism with the soil. The biopolymer at dosages 0.5%, 1%, 1.5%, and 2% was added to the soil. Polyethylene terephthalate Fibre with an aspect ratio of 28 is used with the soil at an increment of 0.4% up to 1.6%. The optimum dosage of biopolymer was mixed with polyethylene terephthalate fibres, and its effect on geotechnical properties was carried out separately. From the experimental investigations, it is comprehended that there is a reduction of 27% and 40% in plasticity index and swelling, respectively, at an optimum dosage of 0.5% GG when compared to untreated soil. Furthermore, there is a marginal decrease of 24% in dry density, 310% increase in CBR value, and 33% reduction in compressibility of the soil treated with 0.5% GG with 1.6% PET fibre, when compared to virgin soil. The present study was conducted to improve the subgrade soil strength beneath the pavements. The usage of biopolymer and its combination with polyethylene terephthalate fibres shows that there is a considerable improvement in modifying the geotechnical properties, and its coupling effect contributes to higher California bearing ratio values. According to the outcomes of this investigation, it is proven that biopolymer and polyethylene terephthalate fibre is definitely an alternate to conventional materials. The present study was conducted to improve the subgrade soil strength beneath the pavements.